2011
DOI: 10.1016/j.jamcollsurg.2010.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Primary Payer Status Affects Outcomes for Cardiac Valve Operations

Abstract: Background Disparities in healthcare have been reported among various patient populations, and the uninsured and Medicaid populations are a significant focus of current healthcare reform. The objective of this study was to examine the influence of primary payer status on outcomes following cardiac valve operations in the United States. Methods From 2003-2007, 477,932 patients undergoing cardiac valve operations were evaluated using discharge data from the Nationwide Inpatient Sample (NIS) database. Records w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 26 publications
0
22
1
Order By: Relevance
“…However, after adjustment for baseline differences between patients and case status, the present study found no association between insurance status and patient outcomes. The difference between our study and the findings of LaPar and colleagues14 and 15 may be due to the single-institution design and unique differences in locoregional or hospital practices that relate to insurance status. For instance, all patients requiring thoracic aortic surgery at our hospital undergo operation by the same team of highly experienced surgeons regardless of insurance status,27 which may contribute to the normalization of operative parameters and outcomes between insured and underinsured patients in our study.…”
Section: Methodscontrasting
confidence: 92%
See 2 more Smart Citations
“…However, after adjustment for baseline differences between patients and case status, the present study found no association between insurance status and patient outcomes. The difference between our study and the findings of LaPar and colleagues14 and 15 may be due to the single-institution design and unique differences in locoregional or hospital practices that relate to insurance status. For instance, all patients requiring thoracic aortic surgery at our hospital undergo operation by the same team of highly experienced surgeons regardless of insurance status,27 which may contribute to the normalization of operative parameters and outcomes between insured and underinsured patients in our study.…”
Section: Methodscontrasting
confidence: 92%
“…Medicaid is jointly funded by state and federal governments and is a health insurance program that provides health insurance for lower-income people, families and children, the elderly, and people with disabilities 12. Medicaid reimburses practitioners at lower rates than other forms of insurance, and patients with Medicaid are generally considered underinsured 13, 14. and 15…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients undergoing coronary artery bypass grafting (CABG) and cardiac valve operations had longer lengths of stay and higher costs if they had Medicaid, as opposed to those with Medicare, private insurance, or no insurance. [11,12]…”
mentioning
confidence: 99%
“…While Medicaid has been associated with worse outcomes in patients with lung cancer, 25 uterine cancer, 26 in patients undergoing cardiac valve operations, 27 and even after lower-extremity injuries, 28 we found that Medicaid was associated with a relative decrease in odds of death when compared to private insurance coverage. Given the inconsistency of our results with the bulk of the literature, which has shown that private insurance is associated with lower mortality than public insurance, we conducted several sub-group analyses.…”
Section: Discussionmentioning
confidence: 55%